ETHICAL PRACTICE OF HEALTH CARE PROFESSIONALS IN HEALTH PROMOTION - Siljak, Sladjana; Boričić, Katarina; Tošić, Mirjana (Srpski medicinski časopis Lekarske komore, 2023)
Health promotion as a process of empowering individuals to improve health in the social environment is based on ethical principles in medical practice and public health and on the responsibility of the social community. Whereas medical ethics dictates the observance of the principles of justice, equality, beneficence, and the respect for patient rights, freedom and personal choice in the process of achieving health care, the patient's environment can cause ‘negative freedom’, stigmatization or restriction of choice, while the provision of an environment that promotes health is primarily considered to be the responsibility of health workers. This review paper deals with the contemporary ethical issues and moral dilemmas that health workers face during health promotion initiatives, whose aim is to enable community residents to make a good personal choice regarding behavior that can help preserve and improve health ("healthy choice"), and to motivate them to achieve their full health potential even when their environment imposes or stimulates different choices. In the reviewed literature, special emphasis is given to the choices that the community regulates in terms of ensuring the realization of the rights and freedoms of patients and the timely dissemination of information, in the context of clinical practice.
Keywords: ethics; health care professionals; medical practice; health promotion; public health